A meta-analysis of COVID-19: Challenging Australiasâ€™ Vocational Education sector - Pearson, Matthew (Journal of Vocational Education Studies, 2020)
With the advent of the digital age, vocational education and associated policy documents can create an awkward marriage for the student and educator.Â  For the student, the move to an online platform of learning containing digital tools is more than just mastery of a program but requires support, to resolve the financial costs and connectivity issues associated with learning in isolation. For the educator, online platforms provide a challenge not only will they became a student to learn the new platform. The educator confronted with new or unfamiliar pedagogical practices vastly different from their past learning experiences. However, the digital divide is complexing with no one issue attributing or resolving the digital divide.